Terahertz spectroscopy on Faraday and Kerr rotations in a quantum anomalous Hall state - Ken N. Okada (Nature Portfolio, 2016)
Quantized magnetoelectric coupling, which induces exotic magneto-optical phenomena, awaits to be evidenced in topological insulators. Here, Okada et al. demonstrate Faraday and Kerr rotations of magnetic topological insulator surfaces in quantum anomalous Hall states by terahertz magneto-optics, indicating topological magnetoelectric effect.